'Clean energy for all': the implementation of Scaling Solar in Zambia. Issue 3 (24th May 2018) - Stritzke, Susann
Abstract : Purpose: The purpose of this paper is to review critical success factors (CSFs) for the implementation of the Scaling Solar Programme in Zambia, the first solar public-private partnership (PPP) in the country. Design/methodology/approach: The single case study is based on stakeholder interviews and the evaluation of primary and secondary sources of data. As a first step, the study illustrates the implementation of Scaling Solar in Zambia and links it to the formal PPP framework of the country. The second step compares central CSFs for PPPs identified by previous research with the current framework of the programme. Furthermore, it analyses whether these CSFs have affected the PPP project implementation in Zambia. Based on these findings the question discussed will be which CSFs can be identified that impacted the implementation of the programme in a third step. Findings: The case study found that the design of the Scaling Solar Programme largely mitigated the main financial and political risks identified in previous studies with regard to the uptake of energy infrastructure processes in developing countries. It reveals that government stakeholder alignment and institutional capacity are the central CSFs which impact the roll-out of the programme in Zambia. Originality/value: The study suggests that a pre-implementation phase of a complex PPP project should comprise government stakeholder alignment which can be based on approaches to Relationship Management Theory. By suggesting a stakeholder management approach, the study indicates how a PPP framework, with a redefined role of a horizontally integrated, independent Public-Private Partnership Unit, can support this approach.